Value addition of meat and milk products - Mendiratta, S. K.; Kandeepan, G. (Indian Farming, 2015)
The Livestock Products Technology Division of IVRI has developed several highly nutritious, ready-to-cook or eat meat and milk products. The LPT Division has made a number of contribution in the area of research and teaching. Emphasis has been given on utilization of low quality meat by utilization in emulsion-based meat products. Restructred meat products is another area where significant contribution has been made by preparing products like nuggets, blocks, rolls and steaks from mutton, pork and buffalo meat. Need based R&D programmes have to be evolved in collaboration with the industry for value-addition of livestock products considering the cost, convenience, quality, nutritive value, health concern etc.